In Vitro Synergistic Interaction between Amphotericin B and Pentamidine against Scedosporium prolificans - Afeltra, Javier (American Society for Microbiology, 2002)
To develop new approaches for the treatment of invasive infections caused by Scedosporium prolificans, the in vitro interaction between amphotericin B and pentamidine against 30 clinical isolates was evaluated using a checkerboard microdilution method based on the National Committee for Clinical Laboratory Standards M38-P guidelines. The interaction between the drugs was analyzed using fractional inhibitory concentration index (FICI) analysis and response surface modeling. Amphotericin B alone was inactive against all the isolates. The geometric mean MIC for pentamidine was 57 μg/ml (range, 8 to 256 μg/ml; MIC at which 50% of the isolates tested were inhibited [MIC(50)], 64 μg/ml; MIC(90), 128 μg/ml). The combination was synergistic against 28 of 30 isolates (93.3%) by FICI analysis and 30 of 30 (100%) by response surface modeling analysis. Antagonism was not observed.